AGE AND INDIVIDUAL CHARACTERISTICS OF PRIMARY SCHOOL STUDENTS AND OPPORTUNITIES FOR DEVELOPING THEIR CREATIVE THINKING - Dadajonova , Azizajon (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This thesis analyzes the development of creative thinking in primary school students, taking into account their age and individual psychological characteristics. The study substantiates the effectiveness of implementing a differentiated approach in the educational process, expanding the cognitive abilities of students, and using innovative methodologies, including cognitive-graphic schemes and interactive games. Furthermore, practical suggestions for forming independent thinking and creativity in primary school children are proposed.